First report of orchid fleck virus and its mite vector on green cordyline - Dietzgen, Ralf G.; Tassi, Aline D.; Freitas-Astúa, Juliana; Kitajima, Elliot W. (Australasian plant disease notes, 2018)
Orchid fleck virus (OFV) and its mite vector Brevipalpus californicus were for the first time identified on green cordyline plants showing distinctive chlorotic and necrotic ringspots. Thin section electron microscopy revealed bacilliform, dichorhavirus-like particles within nuclear viroplasms. RT-PCR using OFV degenerate primers yielded a single amplicon, the nucleotide sequence of which closely matched the nucleoprotein gene of OFV.